Effect of a Dual Intervention with Vitamin D Supplementation and Voluntary Physical Exercise on Cardiac Remodeling and Function in a Mouse Model of Diet-Induced Type 2 Diabetes - Marziou, Alexandra; Philouze, Clothilde; Landrier, Jean-François; Riva, Catherine; Obert, Philippe (Cardiology and Cardiovascular Medicine, 2022)
Background and Aims: We have previously demonstrated the cardiac beneficial effects of vitamin D (VD) supplementation. The aim of this study was to evaluate the combined effects of voluntary Physical Exercise (PE) and VD on cardiac remodeling and function in tertiary prevention in a mice model of diet-induced diabetes. Methods and Results: Mice were fed with a high fat and sucrose diet for 10 weeks. Then, they were divided into 4 subgroups for the 15 following weeks: diet, diet/vitamin D, diet/PE and diet/VD/PE. Glucose homeostasis assessment and echocardiography were performed one week before the end of the protocol. Blood samples and hearts were collected at sacrifice. After 25 weeks of diet alone, obese mice displayed diabetes, cardiac concentric hypertrophy and impaired global and regional myocardial function. PE and VD supplementation had no effect separately on glucose homeostasis but improved cardiac remodeling and preserved cardiac function. Their combination improved glucose homeostasis and was associated with physiological cardiac remodeling, with however no additional beneficial effect over PE or VD alone on cardiac function. Conclusion: The major finding of the present study is that VD supplementation and PE exert similar cardioprotective effects in diabetic mice, with no major synergistic effect from their combination.